Respons Tanaman Angelonia (Angelonia angustifolia) terhadap Pemberian Paclobutrazol - Rugayah Rugayah; Agus Karyanto; Setyo Widagdo; Farida Lukmi (JURNAL AGROTROPIKA, 2023)
Ornamental plants have now developed as souvenirs given at a wedding. Requirements for souvenirs, the plants should be tiny, lush, and have much of flowers. So its growth needs to be modified using a growth regulator paclobutrazol. This study aimed to determine the response of angelonia plants to the application of paclobutrazol at several levels of concentration and determine the concentration of paclobutrazol which has the best appearance of angelonia plants. This research method used a randomized block design (RBD) with treatment of 6 levels of paclobutrazol concentration, namely 0 ppm, 30 ppm, 60 ppm, 90 ppm, 120 ppm and 150 ppm with 3 replications. The F test and further tests were carried out an Orthogonal Polynomials. All tests were carried out at the 5% level. The results showed that the application of paclobutrazol at a concentration level of 30-150 ppm, was effective in suppressing the growth rate of angelonia plants in the vegetative phase. This value was proved by the results of the questionnaire that, the highest visual value was obtained at a concentration of 150 ppm. But with the increasing concentration of paclobutrazol, the freshness of  flowers became shorter. Keywords: Angelonia, Concentration, Paclobutrazol